The Kilwa Coins of Sultan al-Ḥasan ibn Sulaymān in their Historical Context - Smith, N. J. C. (KOINON: The International Journal of Classical Numismatic Studies, 2018)
The history of sub-Saharan Africa is one which is not well known before the coming of the European age of exploration. This is primarily due to a lack of written sources, as many African societies preserved their histories as oral stories and traditions, rather than through writing. While this would have the benefit of kings being able to control information (via their court historians), it has left us with a lack of reliable source material. The oral stories can be used, but only with extreme caution (think of them as a generations-long telephone game, and one can understand how oral tales can be problematic). However, some of East Africa’s oral traditions, which were recorded in the 16th century, have been confirmed by numismatics.